ANALISIS RAGAM PRODUK, HARGA, DAN KUALITAS PRODUK TERHADAPA MINAT BELI KONSUMEN UNTUK UMKM ECENG GONDOK DI KOTA SURABAYA - Salma Mutia Hanifah (ECONOMOS, 2022)
In these millennials era, business is the great opportunity to be able to produce profits, one of its namely entrepreneurship. Entrepreneurship work to increase a series of competition from various aspects with the aim of increasing competitiveness, providing employment, reducing unemployment and poverty. Entrepreneurship is mediated as "passion of developing new businesses". Developed businesses can be independent owned by someone or more entrepreneurs, or they can be developed within the company where they work. Surabaya is one of the locations where small-structured business is built who us known as Micro, Small and Medium Enterprises (MSME), and many MSME training courses are held in this City. The market on being intenses of seeing the diversity and uniqueness of a product issued by a businessman, and also reviewing the price is affordable with good product quality.  Therefore, this study attempts to further explain the analysis of the Product Variety, Price, and Quality of Products on Consumer Buying Interest for MSME of Crafts Eceng Gondok in Surabaya City. This study used a quantitative method, by using questionnaire media as a research instrument instrument. The population in this study is prospective consumers and communities who know about the MSME of Crafts Eceng Gondok in Surabaya City. This study used the purposive sampling method as a sampling technique and established 100 respondents to be sampled. The data analysis technique used is multiple linear regression analysis. The results obtained from the data analysis test on this study show that Product Variety, Price, and Product Quality have a significant influence on Consumer Buying Interest.